Effect of the number of portal area on modified histological activity index of viral hepatitis and histological findings - Gurbuzel, M.; Saygi, G.; Ozyigit, F.; Oguzoncul, A. F.; Gulsen, H. G.; Basaran, S. (Wolters Kluwer Medknow Publications, 2014)
Aim: Viral hepatitis is one of the most important causes of chronic hepatitis. Liver biopsy is used to verify clinical diagnosis and to evaluate necroinflammation and fibrosis. Biopsy is the guide for therapy and can be performed also after treatment to assess the effect of therapy on liver. This paper aimed to explore histopathological characteristics of biopsy samples, which had been referred to our department with the clinical diagnosis of chronic viral hepatitis, in reference to Ishak Modified Hepatic Activity Index (IMHAI), as well as to compare inflammatory scores and stages in the groups created according to the number of portal area (PA). Materials and Methods: The study included 107 patients that underwent liver biopsy in 2011 being diagnosed with chronic viral hepatitis. Age, gender and type of viral hepatitis were retrospectively reviewed and histological findings such as IMHAI inflammatory score and stage, hepatosteatosis and ground glass hepatocytes were re-assessed by two pathologists. Results: Of the present cases, 97 had chronic hepatitis B, 5 had chronic hepatitis C, and 5 had chronic hepatitis BDThe group with PA number of 2-4 consisted of 8 cases and the group with PA number of 11 and over consisted of 37 cases. Conclusion: Statistical analysis performed by comparing IMHAI inflammatory score and stage with PA revealed that score and stage were significantly higher in PA >= 11 groups as compared to PA 2-4 group.
Keywords: Chronic hepatitis; liver biopsy; viral hepatitis